PENGARUH METODE BABY SIGNS DALAM MENINGKATKAN KETEPATAN ARTIKULASI KATA PADA ANAK DENGAN GANGGUAN BAHASA EKSPRESIF - Ganik Nurmawati, Agustina (Widya Warta, 2016)
The purpose of this research is to find out the influence of baby signs method in increasing articulation accuracy on children with expressive language disorder. The subjects of the study are two 4-year-old children with expressive language disorder. The data were collected from the scale of speaking ability. The method used is time series design of quasi experiment, which compares baseline score, posttest score, and follow up score. The data analysis employed quantitative and qualitative techniques. The results showed that baby signs method is able to increase articulation accuracy on children with expressive language disorder.